Controversy of angiotensin receptor blockers (ARBs) and angiotensin converting enzymeinhibitors (ACEIs) prescription for hypertension patients in coronavirus disease 2019 (COVID-19) pandemic - Yuliana Yuliana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Coronavirus disease 2019 (COVID-19) pandemic has made all the world in a mess. Novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causing COVID-19 infects human cells through angiotensin-converting enzyme 2 receptors (ACE receptors). Angiotensin-converting enzyme 2 (ACE) is upregulated in diabetes and cardiovascular diseases including hypertension. Hypertension patients commonly consume angiotensin receptor blockers (ARBs) and/or angiotensin-converting enzyme inhibitors (ACEIs) which could increase ACE receptors. It was suspected that the ARBs or ACEIs administration may worsen the clinical outcome for the hypertension patients with COVID-19. However, no clinical trial had significantly revealed how appropriate management and prescription of ARBs and ACEIs for the hypertension patients with COVID-19. The use of ARBs and ACEIs for these patients is still controversy. Studies concerning the side effect of single or combination use of ARBs and ACEIs in the hypertension patients with COVID-19 as well as specific morbidity and mortality are needed. This review was aimed to provide understanding concerning the appropriate management and prescription of ARBs and ACEIs for hypertension patients with COVID-19.